Curating the City: Begandring Soerabaia and the Production of Public Space - Mazma De Huwrien'in; Purnawan Basundoro (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2025)
This paper examines the role of the heritage community of Begandring Soerabaia in the production of public space employing Henri Lefebvre's concept of social space as a theoretical framework. Focusing on the